SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Oscillatory Dynamics Serving Verbal Working Memory Differ in People with HIV and Are Linked To Disease Duration - Kellen M. McDonald; Seth D. Springer; Mikki Schantell; Ryan Glesinger; Lucy K. Horne; Hannah J. Okelberry; Jason A. John; Anna T. Coutant; Madelyn P. Willett; Hallie J. Johnson; Rachel K. Spooner; Tony W. Wilson (Journal of Neuroimmune Pharmacology, 2025)
Background Medical advances have greatly improved the quality of life and extended the longevity of people with HIV (PWH). However, many PWH still develop neurocognitive deficits even in the presence of effective viral suppression, with impairments in verbal working memory (VWM) being among the most common. While previous neuroimaging studies have demonstrated altered neural responses during VWM, the underlying temporal dynamics and their relation to clinical indices of HIV remain poorly understood. Hypothesis PWH will have altered neural oscillatory dynamics in brain regions supporting VWM compared to controls, above and beyond the effect of age, and these oscillatory differences will scale with clinical indices of HIV. Methods 166 participants (77 virally-suppressed PWH, 89 demographically-matched controls) completed a VWM task during magnetoencephalography, which was separated into encoding and maintenance phases. Whole-brain, mixed-model ANCOVAs were performed to assess the effects of HIV status on neural dynamics controlling for age. Results PWH performed significantly worse on the task compared to controls. During encoding, there was a significant interaction of group-by-time window, such that PWH had significantly weaker alpha/beta oscillations in the left inferior frontal, superior temporal, and anterior cingulate relative to controls. Further, weaker activity in the anterior cingulate scaled with increased disease duration. PWH also displayed weaker alpha/beta oscillations during maintenance in frontal, temporal, parietal, anterior cingulate, and cerebellar cortices. Conclusions PWH exhibited weaker task-related oscillatory activity during VWM, which was associated with disease duration in the anterior cingulate. Overall, these findings suggest that HIV modulates the neural dynamics underlying VWM, with progressive effects in some areas.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Spatially explicit models reveal rodents rapidly colonize soybean fields regardless of pre-planting chemical treatment timing for cover crop removal - Jena L. Nierman; Sean M. Murphy; Wendy Leuenberger; Allison G. Davis; John J. Cox; Matthew T. Springer (Crop Protection, 2024)

Landscape context and behavioral clustering contribute to flexible habitat selection strategies in a large mammal - Nathan D. Hooven; Kathleen E. Williams; John T. Hast; Joseph R. McDermott; R. Daniel Crank; Matthew T. Springer; John J. Cox (Mammal Research, 2024)

Correlates of mid-winter pregnancy and early reproductive outcomes in a reintroduced elk (Cervus canadensis) population - Nathan D. Hooven; Kathleen E. Williams; John T. Hast; Joseph R. McDermott; R. Daniel Crank; Matthew T. Springer; John J. Cox (Mammalian Biology, 2024)

Local and systemic responses to repeated gluteal muscle microbiopsies in mature sedentary horses - Jessica L. Artman; Lauren T. Wesolowski; Pier L. Semanchik; JadaLea K. Isles; Sharon A. Norton; Sarah H. White-Springer (Journal of Equine Veterinary Science, 2024)

Non-native plant invasion after fire in western USA varies by functional type and with climate - Janet S. Prevéy; Catherine S. Jarnevich; Ian S. Pearse; Seth M. Munson; Jens T. Stevens; Kevin J. Barrett; Jonathan D. Coop; Michelle A. Day; David Firmage; Paula J. Fornwalt; Katharine M. Haynes; James D. Johnston; et al. (Biological Invasions, 2024)

High-altitude characterization of the Hunga pressure wave with cosmic rays by the HAWC observatory - Ruben Alfaro; César Alvarez; Juan Carlos Arteaga-Velázquez; Arun Babu Kollamparambil Paul; Daniel Avila Rojas; Hugo Alberto Ayala Solares; Rishi Babu; Ernesto Belmont-Moreno; Chad Brisbois; Karen S. Caballero-Mora; Tomás Capistrán; Alberto Carramiñana; et al. (Advances in Space Research, 2024)

Cryopreservation of Anopheles stephensi (MOSQUITO) EGGS: EFFECTS ON GENOTYPIC AND PHENOTYPIC CHARACTERISTICS - Morgan Douglas; Ehud Inbar; Igor Sharakov; Najib M. El-Sayed; Ashton T. Belew; James Overby; Steve Matheny; Fantahun Addisu; Yonas Abebe; Dimitri Koutzoumis; Kerri Springer; Abraham Eappen; et al. (Cryobiology, 2023)

Refuge‐yeah or refuge‐nah? Predicting locations of forest resistance and recruitment in a fiery world - Kyle C. Rodman; Kimberley T. Davis; Sean A. Parks; Teresa B. Chapman; Jonathan D. Coop; Jose M. Iniguez; John P. Roccaforte; Andrew J. Sánchez Meador; Judith D. Springer; Camille S. Stevens‐Rumann; Michael T. Stoddard; Amy E. M. Waltz; et al. (Global Change Biology, 2023)
Climate warming, land use change, and altered fire regimes are driving ecological transformations that can have critical effects on Earth's biota. Fire refugia—locations that are burned less frequently or severely than their surroundings—may act as sites of relative stability during this period of rapid change by being resistant to fire and supporting post‐fire recovery in adjacent areas. Because of their value to forest ecosystem persistence, there is an urgent need to anticipate where refugia are most likely to be found and where they align with environmental conditions that support post‐fire tree recruitment. Using biophysical predictors and patterns of burn severity from 1180 recent fire events, we mapped the locations of potential fire refugia across upland conifer forests in the southwestern United States (US) (99,428 km 2 of forest area), a region that is highly vulnerable to fire‐driven transformation. We found that low pre‐fire forest cover, flat slopes or topographic concavities, moderate weather conditions, spring‐season burning, and areas affected by low‐ to moderate‐severity fire within the previous 15 years were most commonly associated with refugia. Based on current (i.e., 2021) conditions, we predicted that 67.6% and 18.1% of conifer forests in our study area would contain refugia under moderate and extreme fire weather, respectively. However, potential refugia were 36.4% (moderate weather) and 31.2% (extreme weather) more common across forests that experienced recent fires, supporting the increased use of prescribed and resource objective fires during moderate weather conditions to promote fire‐resistant landscapes. When overlaid with models of tree recruitment, 23.2% (moderate weather) and 6.4% (extreme weather) of forests were classified as refugia with a high potential to support post‐fire recruitment in the surrounding landscape. These locations may be disproportionately valuable for ecosystem sustainability, providing habitat for fire‐sensitive species and maintaining forest persistence in an increasingly fire‐prone world.

Influence of Mechanistic Target of Rapamycin (mTOR)-Regulated Anabolic Pathways on Equine Skeletal Muscle Health - Pier L. Semanchik; Lauren T. Wesolowski; Patrick J. Ryan; Sarah H. White-Springer; James D. Fluckey (Journal of Equine Veterinary Science, 2023)

Cover and density of southwestern ponderosa pine understory plants in permanent chart quadrats (2002–2020) - Margaret M. Moore; Jeffrey S. Jenness; Daniel C. Laughlin; Robert T. Strahan; Jonathan D. Bakker; Helen E. Dowling; Judith D. Springer (Ecology, 2022)
This data set consists of 101 permanent 1 m × 1 m (1‐m 2 ) quadrats located within southwestern ponderosa pine ecosystems near Flagstaff, Arizona, USA. Individual plants in these quadrats were identified and mapped annually for 19 years (2002–2020). The original chart quadrats were established between 1912 and 1927 to determine the effects of domestic livestock grazing on herbaceous plants and pine seedlings. Today these data provide opportunities to examine the effects of climate and land‐use change on plant demography, population dynamics, and community processes. We provide the following data and data formats: (1) digitized maps of all plant locations in shapefile and geodatabase format, (2) shapefiles showing annual locations of each individual plant species, (3) annual maps of each quadrat in TIFF and PDF format, (4) annual basal area of each species per quadrat for species mapped as polygons, (5) tabular representation of polygon areas and centroid locations for plant species mapped as polygons, (6) tabular representation of point locations for plant species mapped as points, (7) plot‐scale 20 m × 20 m overstory tree canopy cover, tree basal area, parent material, and elevation, (8) quadrat‐scale information (e.g., quadrat site and number, coordinates in UTM Zone 12 and latitude/longitude, and descriptive comments for each quadrat), (9) plant species list, (10) summary of plant species observed in each quadrat, (11) summary of quadrats mapped by site and year, and (12) data formatted for use in Integral Projection Models (IPM) and plant population analyses. There are no copyright restrictions; please cite this paper and the associated data set when data are used in publications.

Stakeholder Perceptions of White Oak Supply in Kentucky: A SWOT-AHP Analysis - William R. Thomas; Thomas O. Ochuodho; Chad F. Niman; Matthew T. Springer; Domena A. Agyeman; Laura R. Lhotka (Small-scale Forestry, 2021)

10th Anniversary of the European Association for Predictive, Preventive and Personalised (3P) Medicine - EPMA World Congress Supplement 2020 - Olga Golubnitschaja; Ondrej Topolcan; Radek Kucera; Vincenzo Costigliola; M. Akopyan; S. N. Akulov; O Alexandrova; Angel Alonso; Russell J. Andrews; A Assuane Duarte; O. Azarova; Maximilian Babel; et al. (EPMA Journal, 2020)
In 2019, the EPMA celebrated its 10th anniversary at the 5th World Congress in Pilsen, Czech Republic. The history of the International Professional Network dedicated to Predictive, Preventive and Personalised Medicine (PPPM / 3PM) is rich in achievements. Facing the coronavirus COVID-19 pandemic it is getting evident globally that the predictive approach, targeted prevention and personalisation of medical services is the optimal paradigm in healthcare demonstrating the high potential to save lives and to benefit the society as a whole. The EPMA World Congress Supplement 2020 highlights advances in 3P medicine.

The Mitochondria-Associated ER Membranes Are Novel Subcellular Locations Enriched for Inflammatory-Responsive MicroRNAs - Wang-Xia Wang; Paresh Prajapati; Peter T. Nelson; Joe E. Springer (Molecular Neurobiology, 2020)
The mitochondria-associated endoplasmic reticulum (ER) membranes (MAMs) are specific ER domains that contact the mitochondria and function to facilitate communication between ER and mitochondria. Disruption of contact between the mitochondria and ER is associated with a variety of pathophysiological conditions including neurodegenerative diseases. Considering the many cellular functions of MAMs, we hypothesized that MAMs play an important role in regulating microRNA (miRNA) activity linked to its unique location between mitochondria and ER. Here we present new findings from human and rat brains indicating that the MAMs are subcellular sites enriched for specific miRNAs. We employed subcellular fractionation and TaqMan® RT-qPCR miRNA analysis to quantify miRNA levels in subcellular fractions isolated from male rat brains and six human brain samples. We found that MAMs contain a substantial number of miRNAs and the profile differs significantly from that of cytosolic, mitochondria, or ER. Interestingly, MAMs are particularly enriched in inflammatory-responsive miRNAs, including miR-146a, miR-142-3p, and miR-142-5p in both human and rat brains; miR-223 MAM enrichment was observed only in human brain samples. Further, mitochondrial uncoupling or traumatic brain injury in male rats resulted in the alteration of inflammatory miRNA enrichment in the isolated subcellular fractions. These observations demonstrate that miRNAs are distributed differentially in organelles and may re-distribute between organelles and the cytosol in response to cellular stress and metabolic demands.

Demonstrating developments in high-fidelity analytical radiation force modelling methods for spacecraft with a new model for GPS IIR/IIR-M - S. Bhattarai; M. Ziebart; S. Allgeier; S. Grey; T. Springer; D. Harrison; Z. Li (Journal of Geodesy, 2019)

Habitat heterogeneity drives the host‐diversity‐begets‐parasite‐diversity relationship: evidence from experimental and field studies - Pieter T. J. Johnson; Chelsea L. Wood; Maxwell B. Joseph; Daniel L. Preston; Sarah E. Haas; Yuri P. Springer (Ecology Letters, 2016)
Despite a century of research into the factors that generate and maintain biodiversity, we know remarkably little about the drivers of parasite diversity. To identify the mechanisms governing parasite diversity, we combined surveys of 8100 amphibian hosts with an outdoor experiment that tested theory developed for free‐living species. Our analyses revealed that parasite diversity increased consistently with host diversity due to habitat (i.e. host) heterogeneity, with secondary contributions from parasite colonisation and host abundance. Results of the experiment, in which host diversity was manipulated while parasite colonisation and host abundance were fixed, further reinforced this conclusion. Finally, the coefficient of host diversity on parasite diversity increased with spatial grain, which was driven by differences in their species–area curves: while host richness quickly saturated, parasite richness continued to increase with neighbourhood size. These results offer mechanistic insights into drivers of parasite diversity and provide a hierarchical framework for multi‐scale disease research.

Erratum to: Low ambient oxygen prevents atherosclerosis - Ju-Gyeong Kang; Ho Joong Sung; Marcelo J. Amar; Milton Pryor; Alan T. Remaley; Michele D. Allen; Audrey C. Noguchi; Danielle A. Springer; Jaeyul Kwon; Jichun Chen; Ji-hoon Park; Ping-yuan Wang; et al. (Journal of Molecular Medicine, 2016)

Low ambient oxygen prevents atherosclerosis - Ju-Gyeong Kang; Ho Joong Sung; Marcelo J. Amar; Milton Pryor; Alan T. Remaley; Michele D. Allen; Audrey C. Noguchi; Danielle A. Springer; Jaeyul Kwon; Jichun Chen; Ji-hoon Park; Ping-yuan Wang; et al. (Journal of Molecular Medicine, 2016)

A complete VLBI delay model for deforming radio telescopes: the Effelsberg case - T. Artz; A. Springer; A. Nothnagel (Journal of Geodesy, 2014)

Contrasting effects of sunitinib within in vivo models of metastasis - Jonathan C. Welti; Thomas Powles; Shane Foo; Morgane Gourlaouen; Natasha Preece; Julie Foster; Sophia Frentzas; Demelza Bird; Kevin Sharpe; Antoinette van Weverwijk; David Robertson; Julie Soffe; et al. (Angiogenesis, 2012)

Trend data do support the sequential nature of pinniped and sea otter declines in the North Pacific Ocean, but does it really matter? - J. A. Estes; D. F. Doak; A. M. Springer; T. M. Williams; G. B. Van Vliet (Marine Mammal Science, 2009)

Soil aggregation and carbon sequestration are tightly correlated with the abundance of arbuscular mycorrhizal fungi: results from long‐term field experiments - Gail W. T. Wilson; Charles W. Rice; Matthias C. Rillig; Adam Springer; David C. Hartnett (Ecology Letters, 2009)
We examined the role of arbuscular mycorrhizal fungi (AMF) in ecosystems using soil aggregate stability and C and N storage as representative ecosystem processes. We utilized a wide gradient in AMF abundance, obtained through long‐term (17 and 6 years) large‐scale field manipulations. Burning and N‐fertilization increased soil AMF hyphae, glomalin‐related soil protein (GRSP) pools and water‐stable macroaggregates while fungicide applications reduced AMF hyphae, GRSP and water‐stable macroaggregates. We found that AMF abundance was a surprisingly dominant factor explaining the vast majority of variability in soil aggregation. This experimental field study, involving long‐term diverse management practices of native multispecies prairie communities, invariably showed a close positive correlation between AMF hyphal abundance and soil aggregation, and C and N sequestration. This highly significant linear correlation suggests there are serious consequences to the loss of AMF from ecosystems.

Mammal‐eating killer whales, industrial whaling, and the sequential megafaunal collapse in the North Pacific Ocean: A reply to critics of Springer et al . 2003 - A. M. Springer; J. A. Estes; G. B. Van Vliet; T. M. Williams; D. F. Doak; E. M. Danner; B. Pfister (Marine Mammal Science, 2008)

Case Study Part 1: How to Calculate Appropriate Deterministic Long-Term Toxicity to Exposure Ratios (TERs) for Birds and Mammals - R.F. SHORE; D.R. CROCKER; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; A. FAIRBROTHER; S. FERSON; D. FISCHER; et al. (Ecotoxicology, 2005)

Time transfer using GPS carrier phase: error propagation and results - R. Dach; G. Beutler; U. Hugentobler; S. Schaer; T. Schildknecht; T. Springer; G. Dudle; L. Prost (Journal of Geodesy, 2003)

The international GLONASS experiment: products, progress and prospects - R. Weber; T. A. Springer (Journal of Geodesy, 2001)

Combined processing of the IGS and the IGEX network - D. Ineichen; T. Springer; G. Beutler (Journal of Geodesy, 2001)

Analysis of the first year of Earth rotation parameters with a sub-daily resolution gained at the CODE processing center of the IGS - J. Hefty; M. Rothacher; T. Springer; R. Weber; G. Beutler (Journal of Geodesy, 2000)

Improving the orbit estimates of GPS satellites - T. A. Springer; G. Beutler; M. Rothacher (Journal of Geodesy, 1999)

DNA Sequence Evidence for Placement of the Ground Cuscus, Phalanger gymnotis, in the Tribe Phalangerini (Marsupialia: Phalangeridae) - Aaron T. Hamilton; Mark S. Springer (Journal of Mammalian Evolution, 1999)

A New Solar Radiation Pressure Model for GPS Satellites - T. A. Springer; G. Beutler; M. Rothacher (GPS Solutions, 1999)

Cervical lymphadenitis due to an unusual mycobacterium - E. Tortoli; P. Kirschner; B. Springer; A. Bartoloni; C. Burrini; A. Mantella; M. Scagnelli; C. Scarparo; M. T. Simonetti; E. C. Böttger (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Sex-limited genetic variation in a mouse salivary protein - Robert C. Karn; Stephen R. Dlouhy; Kenneth R. Springer; J. Peter Hjorth; J. Tnnes Nielsen (Biochemical Genetics, 1982)

Aryl hydrocarbon hydroxylase activity in pulmonary alveolar macrophages and lymphocytes from lung cancer and noncancer patients: A correlation with family histories of cancer - T. L. McLemore; R. R. Martin; R. R. Springer; N. Wray; E. T. Cantrell; D. L. Busbee (Biochemical Genetics, 1979)